Sonochemotherapy: From bench to bedside - Bart eLammertink; Clemens eBos; Roel eDeckers; Gert eStorm; Gert eStorm; Chrit eMoonen; Jean-Michel eEscoffre (Frontiers Media S.A., 2015)
The combination of microbubbles and ultrasound has emerged as a promising method for local drug delivery. Microbubbles can be locally activated by a targeted ultrasound beam, which can result in several bio-effects. For drug delivery, microbubble-assisted ultrasound is used to increase vascular- and plasma membrane permeability for facilitating drug extravasation and the cellular uptake of drugs in the treated region, respectively. In the case of drug-loaded microbubbles, these two mechanisms can be combined with local release of the drug following destruction of the microbubble. The use of microbubble-assisted ultrasound to deliver chemotherapeutic agents is also referred to as sonochemotherapy. In this review, the basic principles of sonochemotherapy are discussed, including aspects such as the type of (drug-loaded) microbubbles used, the routes of administration used in vivo, ultrasound devices and parameters, treatment schedules and safety issues. Finally, the clinical translation of sonochemotherapy is discussed, including the first clinical study using sonochemotherapy.